Expressão Imuno-histoquímica das proteínas GLUT-1 e HIF-1α em lesões vasculares de mucosa oral - Oliveira, Denise Hélen Imaculada Pereira de (2012)
The correct histological diagnosis of vascular lesions in the oral mucosa is critical, especially in defining the treatment and prognosis, as some vascular lesions show spontaneous involution and others do not show such behavior. This study analyzed the expression immunohistochemistry of human glucose transporter protein (GLUT-1), in oral benign vascular tumors and to reclassify such lesions according to with his immunoexpression. In addition, we evaluated the immunohistochemical expression of hypoxia-inducible factor 1 alpha (HIF-1α), the main transcription factor involved in cellular adaptation to hypoxia. We analyzed 60 cases of benign oral vascular tumors: 30 cases with histological diagnosis of HEM and 30 cases of oral pyogenic granuloma (PG). The results of this research showed that of the 30 lesions initially classified as HEM, only 7 showed immuno-positivity for GLUT-1, remaining with the initial diagnosis. The remaining 23 were reclassified as vascular malformation (VM) (13 cases) and PG (10 cases). All cases in the sample with an initial diagnosis of PG were negative for GLUT-1, demonstrating the accuracy of histological diagnosis of these lesions. Concerning to the immunoexpression of HIF-1α, the Mann-Whitney test revealed a statistically significant difference between the cases of GP and MV (p = 0.002), where the median of GP (m=78) was higher than the MV (m=53). Based on these results, this study showed that a histological diagnosis alone is not always sufficient for the correct diagnosis of oral HEM and that HIF-1α participates in the pathogenesis of vascular lesions